Spontaneous pneumothorax and bullous emphysema in a young patient? About a case: Neumotórax espontaneo y enfisema bulloso en un paciente joven? A propósito de un caso - Rodriguez-Gutierrez, María Manuela (2023)
Introduction Pneumothorax is a pathology prevalent in traumatic accidents in the thorax, but it can also be found spontaneously due to causes attributable to bullous disease, pneumonia, airway obstruction, malignancy, among others. Case report Young male patient who debuted with spontaneous pneumothorax who required management in the intensive care unit with subsequent appearance of bullae in diagnostic images and pathology. Discussion Primary spontaneous pneumothorax (PSP) in the young population is influenced by psychosocial factors such as age, gender, habits, environment, and genetic factors. In 80% of patients with PSP, the presence of bullae or apical blebs has been demonstrated, in addition from the porosity of the pleura that usually occurs in tall adolescents with athletic bodies; but it is also observed that tobacco use can increase the risk. Conclusions Spontaneous pneumothorax due to bullous emphysema has increased in young people due to the use of psychoactive substances, vapers, and cigarettes.